Quality of life in families under quarantine: a cross-sectional study in seven countries during the first outbreak of COVID-19 - Moya-Salazar, Jeel; Chiu-Higa, Erika; Jaime-Quispe, Alexis; Cañari, Betsy; Moya-Espinoza, Jeel G.; Contreras-Pulache, Hans (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has disrupted human well-being worldwide in unforeseen ways. In early 2020, the spread of the virus left its mark on every affected country, impacting mental health by limiting daily activities and causing fatalities amidst public health strategies to mitigate its impact. The influence of COVID-19 on the quality of life (QoL) may vary between countries, underscoring the need to examine its effects on individuals and families during the mandatory home quarantine. We aimed to assess the QoL of individuals and families during home isolation by COVID-19 lockdown.A cross-sectional study was conducted from February to May 2020. We included adult partners (≥18 years) of families from Brazil,